EXPLORING THE WISDOM OF DISCIPLINE FROM THE NABAWIYAH SIRAH FOR THE MODERN GENERATION - Feighten, Adelia Okta; Sari, Ana Kurnia; Amin, Khoirul (Proceeding of International Conference of Islamic Education, 2024)
This article aims to explore the wisdom of discipline from Sirah Nabawiyah for the modern generation by using a library research approach with descriptive qualitative research, and data sources obtained from books, articles, scientific journals related to disciplinary education in Sirah Nabawiyah. According to language, sirah is the sunnah, way, path and details of life. In terms of terminology, it is a collection of news that is narrated or told about the details of the life of the Prophet Muhammad. The Prophet Muhammad's character has many features, making it easier for us to explore and explore various things related to this side of his life to use as a basis for disciplined character education. In accordance with research results where 50% of character education, there are 2 phases of life that greatly influence one's character, it is necessary to look for values and materials that can be applied to the current disciplined character education process. The results of this research show that the success of character education in this golden age really depends on the parents' ability to restrain themselves and redefine the affection they have always understood for their children. Under any circumstances, parents are expected to be able to design a conducive and natural environment and introduce "living with limitations" to their children. Both will be able to provide a foundation and quality of character, because children are used to observing natural things to know the greatness of the Creator and are used to trying to get something.